First successful treatment of Clostridium perfringens-associated emphysematous hepatitis: a case report - Bayerl, Christian; Berg, Ann-Kathrin; Angermair, Stefan; Kim, Damon; Hamm, Bernd; Beyer, Katharina; Schineis, Christian (Frontiers in Medicine, 2023)
Emphysematous diseases of the abdomen are rare with an often inconspicuous presentation of symptoms and rapid lethal outcome if untreated. We report the first successfully treated case of Clostridium perfringens-associated emphysematous hepatitis. In the emergency room, a 79-year-old man presented with shortness of breath and deteriorated general condition since the morning of admission. Initial CT scans showed a small but rapidly expanding gas collection in liver segment 6. Emergency surgery with atypical liver resection was performed immediately. With early resection and prolonged administration of antibiotics in the presence of sepsis, the patient recovered successfully and was discharged 37 days after admission. As in our case, prompt diagnosis with early surgical treatment is crucial for the management of emphysematous hepatitis.